ANALISIS KOMPONEN BAURAN PROMOSI PADA PERIKLANAN DAN PROMOSI PENJUALAN STARBUCKS - Monalisa MBA (VALUTA, 2016)
ales promotion has a purpose, namely to make the sale quickly and enable customers to buy back(repurchase) and repeat purchases (repeat purchase), in which repurchase and repeat purchase is animportant indicator in the theory of loyalty. Marketing should be designed with the serious in order toincrease sales volume. The marketing activities should be able to attract potential customers to make apurchase to the maximum and thus profits to be achieved can be up anyway. Marketing activities througha company's advertising is an attempt to communicate with the public, which in turn can attract potentialbuyers to purchase the products offered. Promotional activity is one of the company's marketing strategyto get closer to consumers, including advertising, sales promotion, personal selling and publicity. In thisactivity, the company faced with the problem of selection of alternative media are used. So the media willbe used need to be measured its effectiveness, by comparing the benefits gained by spending on suchpromotional activities. A campaign strategy should be adapted to the condition of the company such asthe number of funds available to implement such a strategy, the type of product produced and the natureof the target market faced by the company so that the company can determine the type most suitablepromotional activities to market the product. The media type promotion regarded by the managementcompany may not necessarily be effective if it turns out the media campaign did not support an increasein sales volumes as the company expected. This is indicated by the absence of a reciprocal increase in theexpenditure that has been done by increasing the volume of sales that occurred. For that whether theimplementation of promotional activities have been the right strategy to make the resulting product canstill be accepted or sold in the market so that the company's main goal is to profit by increasing salesvolume can be achieved.